FORMULATION AND DEVELOPMENT OF EXTENDED RELEASED TABLET OF LAMOTRIGINE - MR. AMOL CHAUDHARY; MR. SHARAD PACHARANE; MR. K.R.JADHAV; DR. MR. V.J.KADAM (International Journal of Pharma and Bio Sciences, 2010)
The present study was to develop once-daily extended release tablet of Lamotrigine, an Anticonvulsant. It is a phenyl triazines derivative showing effective anti-convulsant properties mainly used in effective in preventing seizure spread in the maximum electroshock (MES). The tablets were prepared by the wet granulation method. Lamotrigine using hydrophilic matrix material (Methocel K4M & Methocel K100LV) in combination with hydrophobic material (Eudragit L-30D- 55) were used, which can release the drug upto 24hrs in predetermined rate. Diluents used were lactose monohydrate and magnesium starate as lubricant. The influence of hydrophilic and hydrophobic polymer and granulation technique was studied. The formulated tablets were also characterized by physical and chemical parameters. The granules showed satisfactory flow properties, compressibility, and drug content. The in-vitro release rate profile showed the higher concentration of 04-50ERT polymer in tablet, the combination of hydrophilic in core and hydrophobic in coating polymer showed less result than use of a single polymer.